KINERJA PROGRAM STUDI DI STKIP MUHAMMADIYAH SAMPIT - Apuanor Apuanor; Sudarmono Sudarmono; Ayu Lestari (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2019)
This research purpose is to know performance study at STKIP Muhammadiyah Sampit. Subject in this research is Head of Quality Assurance Agency STKIP Muhammadiyah Sampit. Analysis technique use in this research is categorization using average values. Output in this research is to show performance study in the economy study program have a good category with value 64,44%. Guidance and counseling study program have a good category with value 63,61%.